Ibnu Taimiyah and His Concept of Economy - Muhammad Hifdil Islam (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2016)
Human life can not be separated from economic problems which involve human relationships sswith other humans, that relationship must be based on the norms - Islamic religious norms that govern all aspects of life including issues related to mu'amalah. In this context, efforts to develop Islamic economic system, we try to look at a concept that is very brilliant idea at the time, as inspiration and guidance. To the authors try to convey the subject - the subject matter of one of the scholars are: Shaykh al-Islam Ibn Taymiyyah related to economic problems, despite the distance between us and the birth of her very much. He lived at the end of the 7th century and the beginning of the 8th century AH, he has a very deep knowledge about the teachings of Islam. Islam today's economy requires a clear view of what to expect and how things can be done. To achieve this required freedom in business and property rights, which are limited by moral law and supervised by the state fair and able to enforce shari'ah law. All economic activities are allowed, except those expressly prohibited by Shari'ah.